Green Supply Chain Finance: A Bibliometric Review of Financing Instruments, Challenges, and Opportunities - Judijanto, Loso; Utami, Eva Yuniarti; Harsono, Iwan (West Science Interdisciplinary Studies, 2024)
Green Supply Chain Finance (GSCF) has emerged as a pivotal approach for businesses to reconcile financial objectives with environmental sustainability imperatives. This bibliometric review synthesizes the evolving landscape of GSCF literature, analyzing financing instruments, challenges, and opportunities. Leveraging data from 967 papers spanning 1992 to 2024, the review reveals a substantial scholarly interest with a cumulative citation count of 82,996. Through network visualizations and citation analyses, key themes such as sustainable practices, financial innovations, and technology integration are identified. The review underscores the significance of GSCF in advancing sustainable supply chain management and calls for continued research and collaboration to address emerging challenges and capitalize on opportunities.